Utilization of an optimized AlphaFold protein model for structure-based design of a selective HDAC11 inhibitor with anti-neuroblastoma activity - Baselious, Fady; Hilscher, Sebastian; Hagemann, Sven; Tripathee, Sunita; Robaa, Dina; Barinka, Cyril; Hüttelmaier, Stefan; Schutkowski, Mike; Sippl, Wolfgang (Archiv der Pharmazie, 2024)
AlphaFold is an artificial intelligence approach for predicting the three-dimensional (3D) structures of proteins with atomic accuracy. One challenge that limits the use of AlphaFold models for drug discovery is the correct prediction of folding in the absence of ligands and cofactors, which compromises their direct use. We have previously described the optimization and use of the histone deacetylase 11 (HDAC11) AlphaFold model for the docking of selective inhibitors such as FT895 and SIS17. Based on the predicted binding mode of FT895 in the optimized HDAC11 AlphaFold model, a new scaffold for HDAC11 inhibitors was designed, and the resulting compounds were tested in vitro against various HDAC isoforms. Compound 5a proved to be the most active compound with an IC50 of 365 nM and was able to selectively inhibit HDAC11. Furthermore, docking of 5a showed a binding mode comparable to FT895 but could not adopt any reasonable poses in other HDAC isoforms. We further supported the docking results with molecular dynamics simulations that confirmed the predicted binding mode. 5a also showed promising activity with an EC50 of 3.6 µM on neuroblastoma cells.
Keywords: model optimization; Humans; Histone Deacetylase Inhibitors; neuroblastom; histondeacetylasy; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; umělá inteligence; Molecular Docking Simulation; Antineoplastic Agents; AlphaFold; lidé; HDAC11; Histone Deacetylases; molekulární struktura; Drug Design; Artificial Intelligence; Molecular Structure; simulace molekulární dynamiky; inhibitory histondeacetylas; Molecular Dynamics Simulation; racionální návrh léčiv; neuroblastoma; nádorové buněčné linie; protinádorové látky; molecular dynamics simulation; vztah mezi dávkou a účinkem léčiva; Neuroblastoma; Cell Line, Tumor